Clinical evaluation of dental enamel defects and oral findings in coeliac children - Ayşen Yarat; Burçin Alev; Nuray Uslu Kızılkan; Merve Usta; Seap Akyüz; Nafiye Urgancı; Damla Akşi̇t Bıçak (Istanbul University, 2018)
DOI: 10.26650/eor.2018.525Purpose To examine dental hard and soft tissue changes of coeliac children in order to increase the awareness of the pediatric dentists in prediagnosis of especially undiagnosed coeliac disease. Materials and methods Sixty children, 28 (46.7%) boys and 32 (53.3%) girls whose ages were between 6 to 16 years were included in the present study. Thirty children who had undergone endoscopy and diagnosed with the coeliac disease in the Şişli Hamidiye Etfal Hospital, İstanbul, Turkey, formed the study group. Also, thirty children clinically suspected of having the coeliac disease with the same gastrointestinal complaints had undergone endoscopy and proven not coeliac were chosen as the control group. Oral examination involved assessment of dentition and specific and unspecific dental enamel defects. Also, soft tissue lesions, clinical delay of the dental eruption, salivary flow rate, pH, and buffering capacity were examined. Results Twenty coeliac patients had enamel defects, however none in the control subjects. In the coeliac group, all enamel defects were diagnosed in permanent teeth and as specific in all children. Grade I dental enamel defects found mainly in the incisors. The clinical delayed eruption was observed in 10 (33.3%) of 30 coeliac children and none of the children in the control group. While the level of DMFT/S numbers and stimulated salivary flow rate were found significantly lower in the coeliac group, pH was found significantly higher. Conclusion Oral cavity may be involved in coeliac disease and pediatric dentists can play an important role in the early diagnosis of the coeliac disease.